Fiscal policy coordination in a monetary union. Case of fiscal con-vergence criteria and their influence on national accounts and the balance of payments - Zelez Alexander (My University, 2007)
A monetary union can exist without a centralized government and member countries having to give up their individual fiscal policies. Fiscal convergence criteria are utilized in case of monetary unions, whose member countries have not abandoned the power to issue and influence national fiscal policy as opposed to the functioning of an optimum currency area. They undertake the form of hard restrictions of individual policy issuance in member states and strict fiscal guidance towards macroeconomic and monetary stability. However, a spendthrift attitude of fiscal authorities and imprudent government spending behavior can only be avoided if a multilateral surveillance mechanism is implemented in the monetary union. A mutual control procedure initiated by a supranational body is necessary to monitor public expenditure and to counteract further emergence and increase of current account deficits and public debt. Successful fiscal coordination on a national level leads to symmetry between member countries. The correlation of member countries’ business cycles is of utmost importance for the well-being of the entire monetary union. Aim of the thesis: recognize nature of fiscal policy coordination in monetary unions Hypothesis 1: if a monetary union introduces fiscal coordination it may influence na-tional accounts and a balance of payments. Hypothesis 2: differences in fiscal convergence criteria among monetary unions could be a result of different exchange rate regimes.
Koordynacja polityki fiskalnej w unii monetarnej. Kryteria konwergencji fiskalnej oraz ich wpływ na rachunki narodowe i bilans płatniczy
Keywords: fiscal policy; monetary union; fiscal convergence; national accounts; balance of payments; GDP; BOP